The legend of Brightblade - Aldridge, Ethan M. (Quill Tree Books, an imprint of HarperCollinsPublishers, 2022)
"Prince Alto dreams of being a hero like his mother, the Lady Brightblade. Her well-known legend was woven into stories by the magical bard who fought by her side...He has been learning the bard's magic, and has grown restless with royal life. Determined to have an adventure of his own, Alto runs away from the palace. On his journey, he finds himself making new friends and encountering new and exciting magic...[but] discovers that there are dangers threatening the kingdom"--Provided by publisher.